The relationship between strategic planning and organizational performance: examining the moderating effect of transformational leadership / Waleed Abdulkafi Ahmed - Abdulkafi Ahmed, Waleed (Institute of Graduate Studies, UiTM, 2017)
This study was to examine the relationship between strategic planning (consists of three dimensions strategic planning level, strategic planning implementation and strategic planning barriers) and organizational performance. It examined also the moderating effects of transformational leadership on the relationship between strategic planning (consists of three dimensions strategic planning level, strategic planning implementation and strategic planning barriers) and organizational performance in Yemen banks. The data was collected through self-administered questionnaires from 246 respondents who were the top and middle management staff of Yemen Banks with the percentage of 61.5%. This data was further analyzed using mainly the Structural Equation Modelling (SEM) to investigate causal and moderating relationships between latent variables utilizing the SmartPLS. The results revealed that all of the strategic planning dimensions were significantly and positively related to organizational performance…